A good servant but a bad master: Finnish Translators’ Perceptions on Translation Technology - Salmi Leena (France, 2025)
This paper reports the results of a survey measuring Finnish professional translators’ (N=450) perceptions on translation technology. The paper also introduces a tool that can be used to study the perception of such changes, the NEMP model (New Educational Models or Paradigms). Main results indicate that translation technology is perceived by professional translators as an efficient tool that has changed translating in practice, but does not encourage to creativity. Business translators seem to have a more positive perception on translation technology than other respondents (literary or audiovisual translators). As for the method, the results indicate that the NEMP model is a useful method for studying the perception of translation technology. Keywords: professional translators; translation technology; CAT tools; efficiency; attitudes